Handling Florida Vegetables Series - Round and Roma Tomato Types - Steven A. Sargent; Jeffrey K. Brecht; Qingren Wang; Teresa Olczyk (EDIS)
If picked at the proper mature-green stage and handled properly, tomatoes will ripen to excellent edible quality. Proper postharvest handling of Florida tomatoes is critical to ensure the continued competitiveness of Florida growers.This publication focuses on round and roma (plum) tomatoes since these types are handled similarly under commercial conditions. Originally published August 1989. Revised November 2005, by Steven A. Sargent, Jeffrey K. Brecht, and Teresa Olczyk. This update December 2014 with Qingren Wang.